UCHL1 from serum and CSF is a candidate biomarker for amyotrophic lateral sclerosis - Li, Ruibing (Ann Clin Transl Neurol, 2020)
OBJECTIVE: To identify potential ALS biomarkers in patients and to evaluate their diagnostic performance using cerebrospinal fluid (CSF) and serum. METHOD: We recruited a discovery cohort, comprising 20 ALS patients and 20 controls to screen for potential CSF biomarker, UCHL1, using a Luminex neurodegenerative disease panel. To validate UCHL1’s diagnostic performance, we used receiver operating characteristic (ROC) curves to determine the potential for early diagnosis in another cohort comprising 23 CSF and 69 serum ALS samples. Finally, we analyzed its correlation with clinical features. RESULTS: We found significantly elevated levels of CSF‐derived UCHL1 in both discovery and validation cohorts (P < 0.05). ROC curves revealed an AUC of 0.8288, with a sensitivity and specificity of 73.91% and 81.25%, respectively, when the cut‐off value for UCHL1 was >291.9 pg/mL. A similar result was observed in the serum cohort, with the ALS group exhibiting significantly higher serum UCHL1 levels than the controls (P < 0.05). AUC of the ROC in the serum UCHL1 cohort was 0.7709, with sensitivity and specificity of 61.43% and 79.59%, respectively, when the cut‐off value of serum UCHL1 was >15.22 pg/mL. At the early stage CSF and serum UCHL1 were significantly different between ALS patients and controls (P < 0.05). Furthermore, serum UCHL1 levels showed a positive relationship with the burden of UMN and LMN dysfunction, albeit with no statistical significance. INTERPRETATION: Taken together, our findings suggest that ALS patients exhibit significantly elevated CSF‐ and serum‐derived UCHL1. Moreover, our data warrant that UCHL1 displays good diagnostic performance and provide novel options for ALS early diagnosis. However, its prognostic value needs to be further investigated.